(3R,4R,5R)-5-(Acetamido-meth-yl)-N-benzyl-3,4-dihy-droxy-tetra-hydro-furan-3-carboxamide. - Simone, M; Edwards, A; Cowley, A; Fleet, G; Watkin, D (2010)
X-ray crystallographic analysis with Cu Kα radiation established the relative configurations of the stereogenic centers in the title compound, C(15)H(20)N(2)O(5), and clarified mechanistic ambiguities in the synthesis. The conformation of the five-membered ring approximates twisted, about a C-O bond. The absolute configuration of this carbon-branched dipeptide isostere was known based on the use of d-ribose as the starting material. Refinement of the Flack parameter gave an ambiguous result but the refined Hooft parameter is in agreement with the assumed (d-ribose) absolute structure. The crystal structure consists of N-H⋯O and O-H⋯O hydrogen-bonded bi-layers, with the terminal methyl and phenyl groups forming a hydro-phobic inter-layer inter-face. Some weak C-H⋯O inter-actions are also present.